1999
DOI: 10.1128/iai.67.2.589-594.1999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition ofStaphylococcus aureusAdherence to Collagen under Dynamic Conditions

Abstract: Staphylococcus aureus is the most common etiological agent of bacterial arthritis and acute osteomyelitis and has been shown to bind to type II collagen under static and dynamic conditions. We have previously reported the effect of shear on the adhesion ofS. aureus Phillips to collagen and found that this process is shear dependent (Z. Li, M. Höök, J. M. Patti, and J. M. Ross, Ann. Biomed. Eng. 24[Suppl. 1]:S–55). In this study, we used recombinant collagen adhesin fragments as well as polyclonal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…One study reported that fluid shear-induced detachment of S. aureus from fibrinogen (range 1000-7000 s −1 ) did not change significantly with increasing shear force (Dickinson and Cooper, 1995). However, in our laboratory, we previously demonstrated that shear force alone did not cause S. aureus detachment from collagen (Mohamed et al, 1999). Based on these combined findings, we hypothesized that shear force would act synergistically with a destabilizing antibody to increase detachment.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…One study reported that fluid shear-induced detachment of S. aureus from fibrinogen (range 1000-7000 s −1 ) did not change significantly with increasing shear force (Dickinson and Cooper, 1995). However, in our laboratory, we previously demonstrated that shear force alone did not cause S. aureus detachment from collagen (Mohamed et al, 1999). Based on these combined findings, we hypothesized that shear force would act synergistically with a destabilizing antibody to increase detachment.…”
Section: Introductionmentioning
confidence: 79%
“…The CNA (S. aureus collagen receptor) mouse monoclonal antibody (mAb) 9G7 isotype IgG 1 was used as the destabilizing mAb and was a gift from Dr. Joseph Patti, Inhibitex, Atlanta, GA and Dr. Pietro Speziale, Universita di Pavia, Pavia, Italy. Previous reports have demonstrated that only specialized antibodies to the collagen receptor promote destabilization in a static or fluid shear system (Mohamed et al, 1999;Visai et al, 2000). Monoclonal antibody 9G7 has been shown to block collagen binding to S. aureus Cowan-1, displace previously bound collagen from Cowan-1 in solution, and displace Cowan-1 initially bound to a collagen substrate in static assays (Visai et al, 2000).…”
Section: Antibody Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate that attention must be taken in choosing the growth method used to measure biofilm production by S. epidermidis in order to make meaningful comparisons among different investigations. Biofilm formation by medically relevant S. epidermidis is used in many studies, including those looking for molecular and cellular correlates of biofilm formation (Heilmann et al 1996;Cramton et al 1999;Galbart et al 2000), in studies concerning prevention of biofilm formation by antimicrobial agents (Rupp and Hamer 1998) or to evaluate some host immune factors (Mohamed et al 1999). As many of these studies attempt to evaluate the role of PNAG in the pathogenesis of infection and in biofilm formation properties, the use of static-batch systems may not be suitable.…”
Section: Discussionmentioning
confidence: 99%